SINTESIS POLIEUGENOL DARI EUGENOL DENGAN KATALIS ASAM NITRAT PEKAT DAN MEDIA NATRIUM KLORIDA - Suirta, I Wayan; Rustini, Ni Luh; Iqbal Prakasa, Taka (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 1 Januari 2012)
Polyeugenol has been synthesized from eugenol by using nitric acid as a catalyst and sodium chloride medium. Eugenol was obtained from clove oil which was previously redestill. The synthesis was carried but by using nitric acid catalyst on sodium chloride medium and without sodium chloride. The ratio of nitric acid to eugenol as 4 : 1. Polymerization result was analyzed by using infrared spectroscopy. Its rendement and its characteristics were also. The yield with sodium chloride medium was 42,97 %, a reddish black gel with melting point of 114,6-150oC. The yield without sodium chloride medium was 47,77 %, a solid brick red with melting point of 87-89oC. The infrared spectroscopy result showed that on the polymerization with medium was unsuccessful because the still CH=CH2 group absorption at 995.27 cm-1 and C=C at 1635,89 cm-1 were still existed, whereas for the polymerization without medium, both absorptions were absent.
Keywords: eugenol, polieugenol, nitric acid, sodium chloride